2019
DOI: 10.1111/jdi.13148
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum level and impaired response to glucose fluctuation of asprosin is associated with type 2 diabetes mellitus

Abstract: Aims/Introduction Asprosin is a novel secreted adipokine that is induced by fasting and promotes hepatic glucose release. In healthy humans, circulating asprosin shows circadian oscillation with an acute drop coinciding with the onset of eating. The present study investigated whether this circadian oscillation still exists in patients with type 2 diabetes mellitus. Materials and Methods We recruited 60 patients with type 2 diabetes mellitus and 60 individuals with normal glucose tolerance (NGT). All participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 21 publications
15
71
1
1
Order By: Relevance
“…In addition, a hospitalbased case-control study including 170 subjects also showed higher serum asprosin concentrations in adults with T2DM when compared with controls, and independent association between fasting glucose and serum asprosin in T2DM, which is consistent with numerous studies (14)(15)(16)(17). Furthermore, there is an impaired or blunted response of serum asprosin levels to the fluctuation of blood glucose in type 1 diabetes mellitus (T1DM) and T2DM patients (16,18). Recently, it has been reported that the serum asprosin levels of pregnant women with GDM and their newborns' umbilical cords are higher than controls (19).…”
Section: Asprosin In Diabetessupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, a hospitalbased case-control study including 170 subjects also showed higher serum asprosin concentrations in adults with T2DM when compared with controls, and independent association between fasting glucose and serum asprosin in T2DM, which is consistent with numerous studies (14)(15)(16)(17). Furthermore, there is an impaired or blunted response of serum asprosin levels to the fluctuation of blood glucose in type 1 diabetes mellitus (T1DM) and T2DM patients (16,18). Recently, it has been reported that the serum asprosin levels of pregnant women with GDM and their newborns' umbilical cords are higher than controls (19).…”
Section: Asprosin In Diabetessupporting
confidence: 89%
“…Asprosin was positively associated with the homeostasis model assessment for IR (HOMA-IR), while negatively related to the homeostasis model assessment for β-cell function (HOMA-β) (14). In addition, a hospitalbased case-control study including 170 subjects also showed higher serum asprosin concentrations in adults with T2DM when compared with controls, and independent association between fasting glucose and serum asprosin in T2DM, which is consistent with numerous studies (14)(15)(16)(17). Furthermore, there is an impaired or blunted response of serum asprosin levels to the fluctuation of blood glucose in type 1 diabetes mellitus (T1DM) and T2DM patients (16,18).…”
Section: Asprosin In Diabetessupporting
confidence: 88%
“…Another observation was a significant increase in plasma glucose concentrations in the wild rice fed mice as compared to that in the control group. Increased plasma glucose levels are seen during diabetes or insulin resistance in animals as well as humans [37,38]. However, the consumption of high fiber diets is generally recommended to combat complications that are caused by diabetes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Так, Zhang и соавт. отметили положительное антифибротическое действие аспросина на миокард в постинфарктный период [21].…”
Section: роль дисфункции аспросина в патологии человека и перспективыunclassified